A DOC2 protein identified by mutational profiling is essential for apicomplexan parasite exocytosis. - Farrell, A; Thirugnanam, S; Lorestani, A; Dvorin, J; Eidell, K; Ferguson, D; Anderson-White, B; Duraisingh, M; Marth, G; Gubbels, M (2012)
Exocytosis is essential to the lytic cycle of apicomplexan parasites and required for the pathogenesis of toxoplasmosis and malaria. DOC2 proteins recruit the membrane fusion machinery required for exocytosis in a Ca(2+)-dependent fashion. Here, the phenotype of a Toxoplasma gondii conditional mutant impaired in host cell invasion and egress was pinpointed to a defect in secretion of the micronemes, an apicomplexan-specific organelle that contains adhesion proteins. Whole-genome sequencing identified the etiological point mutation in TgDOC2.1. A conditional allele of the orthologous gene engineered into Plasmodium falciparum was also defective in microneme secretion. However, the major effect was on invasion, suggesting that microneme secretion is dispensable for Plasmodium egress.